DNA damage in HeLa cells induced arrest at a discrete point in G2 phase as defined by CENP-F localization. - Fletcher, L; Yen, T; Muschel, R (2003)
G(2) is defined as the time in the cell cycle after DNA synthesis is complete but before the initiation of mitosis. However, as the molecular events of the cell cycle are described, G(2) can be seen to be a sequence of events rather than a static phase. For example, CENP-F increases in amount in early G(2), after DNA synthesis is complete, but localizes to the nuclear rim and then to the kinetochores before mitosis commences. After DNA damage cells may arrest in G(2) through TP53-dependent and independent mechanisms, raising the question of the precise position of the arrest within G(2). HeLa cells lack functional TP53; this allowed us to examine the TP53-independent mechanism of G(2) arrest. Here we showed that the DNA damage-induced G(2) arrest in HeLa cells is positioned in early G(2), before redistribution of CENP-F to the nuclear envelope and kinetochores, and before chromosome condensation commences.